Prediction of Emotional Empathy in the Wives of Veterans by Cognitive Emotion Regulation Strategies and Resilience - M. Moghanloo; S.M. Hosseini (Afarand Scholarly Publishing Institute, 2019)
Aims: After the end of the war and the return of the warriors to the family, due to the stresses of the war and its devastating effect on the peoplechr('39')s spirits, the adverse effects of war on the family, especially their wives, continue. The aim of this study was the prediction of emotional empathy by cognitive emotion regulation strategies and resilience in the wives of veterans. Instruments and Methods: In this descriptive-correlational study, 306 veterans' spouses, who were referred to counseling center of the foundation of martyrs and veterans affairs in Robat Karim in 2016, were selected by simple random sampling method. The research instrument included Lodischr('39')s emotional empathy questionnaire, Garnefski's cognitive emotion regulation, and the Connor-Davidson Resilience Scale (CD-RISC). The data were analyzed by SPSS 21, using Pearson correlation coefficient and multiple regression test. Findings: There was a positive and significant correlation between positive cognitive emotion regulation (r=0.73) and resiliency (r=0.99) with emotional empathy (p=0.001), but there was no significant correlation between negative cognitive emotion regulation and emotional empathy (p=0.418). Among predictor variables, only resilience and positive cognitive emotion regulation strategies were able to positively and significantly predict emotional empathy in veterans' spouses (p<0.05). Coclusion: positive cognitive emotion regulation strategies and resilience can positively predict emotional empathy in veterans' spouses